Rules regarding the hearing of the defendant - Buzescu, Adelin-Alexandru (Technium Social Sciences Journal, 2023)
The defendant is the person against whom the criminal action was initiated. The defendant is a part of the criminal incrimination process, both during the criminal investigation and during the preliminary phase or trial phase, being a passive subject of both the criminal investigation and the civil action taken. Authors, co-authors, accomplices, instigators of the crime in the form of a consummated or exhausted attempt, who have criminal capacity, can be accused. Both physical and legal persons can be defendants. One or more persons can acquire the quality of defendants during the criminal investigation. The purpose of the work is to show the important role of taking the defendant's statements and the way of listening to them by the judicial bodies. Unlike the statements of the injured person, which can be considered as having, in principle, more credibility and probative value, the statements of the defendants cannot have this characteristic, taking into account on the application of the procedural provisions and the consideration of the mental resources that determine each category of participants to process of adopting a sincere position or, on the contrary, insincere. With regard to the way of listening to the defendant, we will note that the New Code of Criminal Procedure provides that the following rights and obligations must be made known to him for the first time: the right not to give any statement during the criminal trial, the right to consult the file, the right to have a chosen lawyer, the right to propose the administration of evidence , the obligation to appear at all the summons of judicial bodies, the obligation to communicate any change of address, the obligation to tell the truth.